TECHNICAL AND CARTOGRAPHY STUDY OF DELIMITATION MANAGEMENT LIMITS AREA OF THE SEA CENTRAL SULAWESI PROVINCE AND NORTH MALUKU - Kurniawan, Agung (Jurnal Ilmu Kelautan SPERMONDE, 2019)
As one of the countries that have a regional autonomy policy, Indonesia gives authority to regional governments to implement and manage the wealth of natural resources in the region, including the potential and wealth of marine resources. The basic juridical area in carrying out natural resource management which is the authority of the regions is set out in Law No. 23 of 2014 which is a revision of the previous Law, namely Law No. 32 of 2004. Local governments have the right to conduct the management of marine resources with an area of 12 miles drawn from the position of the baseline towards the Indonesian archipelago waters. One segment of the sea area management boundary that needs to be resolved is in the Maluku sea region, namely Central Sulawesi Province and North Maluku. This study aims to provide an alternative sea level management line between Central Sulawesi and North Maluku Provinces. The method used to produce the boundaries of marine management areas is the Equidistance Principles method (equal distance) using the basepoint to basepoint. The results show that the lines produced through the boundary withdrawal process using the basepoint to basepoint approach look different when compared to the sea boundary lines that are on the national marine environment map